Reforming Marriage Registration Policies in Malaysia and Indonesia - Warman, Arifki Budia; Jafar, Wahyu Abdul; Asmara, Musda; Kirin, Arwansyah bin; Usmani, Sheikh Adnan Ahmed (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2023)
This study aims to explain the reform of marriage registration policies in Indonesia and Malaysia. Marriage registration policies in Indonesia and Malaysia have yet to be appropriately implemented. This is proven by the fact that many unregistered marriage practices exist. This study is a literature and field research. Data was collected through documentation and interviews. This study found that the States of Indonesia and Malaysia have issued policies regarding the mandatory registration of marriages. Even so, there are still many unregistered marriages. There are many factors behind the occurrence of unregistered marriages, besides also causing problems. The government needs to reform the marriage registration policy, one of which is through digitalization. The State of Indonesia has innovated marriage registration, namely, online registration of marriages. However, this policy was implemented less effectively below. Meanwhile, the Malaysian state still needs to renew its marriage registration policy. Therefore, in this digital era, it is necessary to have a policy for registering marriages in the direction of complete digitization so that problems can be appropriately resolved.